Interleukin-21 Enhances Rituximab Activity in a Cynomolgus Monkey Model of B Cell Depletion and in Mouse B Cell Lymphoma Models - Krejsa, Cecile M.; Holly, Rick D.; Heipel, Mark; Bannink, Ken M.; Johnson, Rebecca; Roque, Richard; Heffernan, Jane; Hill, Julie; Chin, Lay; Wagener, Felecia; Shiota, Faith; Henderson, Katherine; et al. (PLOS ONE, 2013)
Rituximab, a monoclonal antibody targeting CD20 on B cells, is currently used to treat many subtypes of B cell lymphomas. However, treatment is not curative and response rates are variable. Recombinant interleukin-21 (rIL-21) is a cytokine that enhances immune effector function and affects both primary and transformed B cell differentiation. We hypothesized that the combination of rIL-21 plus rituximab would be a more efficacious treatment for B cell malignancies than rituximab alone. We cultured human and cynomolgus monkey NK cells with rIL-21 and found that their activity was increased and proteins associated with antibody dependent cytotoxicity were up-regulated. Studies in cynomolgus monkeys modeled the effects of rIL-21 on rituximab activity against CD20 B cells. In these studies, rIL-21 activated innate immune effectors, increased ADCC and mobilized B cells into peripheral blood. When rIL-21 was combined with rituximab, deeper and more durable B cell depletion was observed. In another series of experiments, IL-21 was shown to have direct antiproliferative activity against a subset of human lymphoma cell lines, and combination of murine IL-21 with rituximab yielded significant survival benefits over either agent alone in xenogeneic mouse tumor models of disseminated lymphoma. Therefore, our results do suggest that the therapeutic efficacy of rituximab may be improved when used in combination with rIL-21.